The cannabis class: What happened when the legal status of cannabis was reclassified?. Issue 5 (29th October 2013) - Hamilton, Ian
Abstract : The states of Washington and Colorado have passed laws legalising the recreational use of cannabis from next year. Will the effect be disastrous for mental health, or cool? In Britain, cannabis was reclassified in 2004 from a class B drug to the less serious class C; but in 2008 it was again reclassified, back to class B.Ian Hamilton looks at what followed.